El Excentrico, 1956-01-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
Janurary 5, 1956 [5 de enero de 1956]. Ano 6, No. 5. Cover has photos of muscial band leader, Vincent Hermosillo attempting a weight loss regime as part of his New Year's resolution. The headline reads, "Band Leader Vincent Hermosillo" New Year's Resolution..."